Adhesion and motility of gliding bacteria on substrata with different surface free energies. - Burchard, R P (1990)
The adhesion and motility of several aquatic and terrestrial gliding bacteria on slides differing in their critical surface energies have been examined. In general, adhesion was tenacious on low-critical surface energy (hydrophobic) surfaces and tenuous on hydrophilic surfaces. Gliding was inhibited on very hydrophobic substrata and skittish on very hydrophilic surfaces.